Brain tumor postoperative nursing - Muñoz S., Violeta-Luz; Euribe S., Maria Teresa; Ponce Valencia, Alicia; Cabanillas-Chavez, María Teresa; Morales-García, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Invasive mechanical ventilation is one of the methods most used in intensive care units, which leads to a process of quitting it, which is known as weaning. In this document, a standardized care plan was made, using the methodology of the nursing process, where an adequate protocol for patient care has been established and that represents a useful tool for the health professional and facilitates safe, quality care, based on evidence. Objective : to describe the assessment performed on the patient to determine the main diagnosis "Dysfunctional ventilatory response to weaning r / c history of ventilator dependence 3 days m / p increase in heart rate compared to baseline". Discussion : in general, most of the evidence, the authors agree with the results and conclusions : Synthesizing the resolution of the case coincides in their daily practice with the scientific evidence found, both weaning from mechanical ventilation and its complications, some of them performed each. The role of the nurse is essential for patient care, reducing the risk of complications in the removal of the ventilator.